2006
DOI: 10.1002/app.23366
|View full text |Cite
|
Sign up to set email alerts
|

Molecular transport of aliphatic hydrocarbons through styrene butadiene rubber/ethylene vinyl acetate blends

Abstract: ABSTRACT:Polymer blends based on styrene butadiene rubber and ethylene vinyl acetate (EVA) were prepared. The sorption and diffusion of four aliphatic hydrocarbons through the blends were investigated with temperatures of 26 -56°C. Sulfur, dicumyl peroxide (DCP), and a mixed system consisting of sulfur and DCP (mixed) were used as crosslinking agents for the blends. Of the three systems, the peroxide vulcanized blends were found to exhibit the lowest penetrant uptake. The aliphatic liquid penetration through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has been reported that the permeation depends upon a number of factors like composition, method of formation, type of cross linking agents used, nature and size of the penetrants, temperature etc. For example, a decrease in diffusivity with an increase in the size of penetrant has been reported by many investigators 10,11 .…”
Section: Introductionmentioning
confidence: 76%
“…It has been reported that the permeation depends upon a number of factors like composition, method of formation, type of cross linking agents used, nature and size of the penetrants, temperature etc. For example, a decrease in diffusivity with an increase in the size of penetrant has been reported by many investigators 10,11 .…”
Section: Introductionmentioning
confidence: 76%
“…where, ρ p is the density of the polymer, V S is the molar volume of the solvent, φ is the volume fraction of the polymer in the fully swollen state, and χ is the polymer−penetrant interaction parameter determined as suggested by different researchers. 23,24 The estimated values of M c are given in Table 3. From the table, it can be seen that the M c values decrease with increase in the HDPE content in the blends, for a given filler in accordance with the solvent uptake behavior.…”
Section: Resultsmentioning
confidence: 99%
“…These observations can also be explained using cross-link density and molar mass between the cross-links for the different vulcanizing systems. The molar mass between cross-links ( M c ) of the network polymer chain was calculated using the Flory–Rehner relation M c = ρ P V S false( φ 1 / 3 φ / 2 false) ln false( 1 φ false) + φ + χ φ 2 where, ρ p is the density of the polymer, V S is the molar volume of the solvent, φ is the volume fraction of the polymer in the fully swollen state, and χ is the polymer–penetrant interaction parameter determined as suggested by different researchers. , The estimated values of M c are given in Table . From the table, it can be seen that the M c values decrease with increase in the HDPE content in the blends, for a given filler in accordance with the solvent uptake behavior.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a decrease in the diffusivity with an increase in the size of penetrant has been reported by many investigators. 1214 Haraya and Hwang 15 have conducted permeation studies in a series of polymers for selecting appropriate polymers for the separation of O 2 /Ar mixtures. Masoud et al 16 studied gas barrier properties of Polypropylene (PP)/ethylene propylene diene monomer (EPDM) blend composite and found that the permeability decreased with PP content in the composite.…”
Section: Introductionmentioning
confidence: 99%